Analysis of potential benefit and maturity level of digital procurement - Sascha Stradner; Uwe Brunner (Changing Tides: The New Role of Resilience and Sustainability in Logistics and Supply Chain Management – Innovative Approaches for the Shift to a New Era. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 33, 2022)
Purpose: Procurement departments are facing major challenges of digitalization. To meet future business requirements, managers are forced to arrange investments for the digitalization of procurement processes. Current studies show that the maturity level of procurement digitalization is still lacking due to missing benefit assessments of investments. Methodology: For this purpose, the benefit potentials of digitalized procurement are analyzed based on a systematic literature analysis, followed by qualitative expert interviews to evaluate hypotheses derived from the literature. Moreover, the expert interviews provide information about the current maturity level of digitalization in procurement. Findings: The systematic literature analysis and qualitative expert interviews provide 24 potential benefits, which are summarized in six categories. The expert interviews indicate that increasing of efficiency, process transparency and data quality are seen as the main benefit potentials of digital procurement. In terms of maturity, the experts confirm potentials that need to be exploited to enable future procurement at competitive prices. Originality: Current research on digital procurement is forcing superficial concepts of digitalization measures. A well-founded assessment of potential benefits of the implementation in companies is still missing, which leads to critical barriers in digitalization and missing adaption to rapidly changing market conditions.
urn:nbn:de:gbv:830-882.0200917; hdl:10419/267179; https://econpapers.repec.org/RePEc:zbw:hiclpr:33
Keywords: 650; Innovation Management; Technology Management